PROTOTYPE ROAD GUIDE TOOL FOR BLIND PEOPLE BASED ON FUZZY LOGIC - Mhd. Furqan; Rakhmat Kurniawan; Siti Sarah Harahap (INFOKUM, 2022)
One of the physical limitations that exist in humans is blindness. Because it is difficult to see, they need tools to help them carry out their daily activities. A tool is needed to help guide them in walking activities. A walking guide tool for blind people based on fuzzy logic is one solution to help them in walking activities. By using a microcontroller as a controller of the ultrasonic sensor, buzzer, DC motor, and water sensor. The ultrasonic sensor is used to read the objects in front of the tool and provide this information to the microcontroller. The data sent by the sensor to the microcontroller will be processed and send sound information (buzzer) and vibrations (DC motor) when the ultrasonic sensor detects an object with a predetermined distance to the visual impaired. This guide tool for visually impaired persons uses fuzzy logic as a control system, by applying the fuzzy logic method to the blind aids to be able to provide logic output to the objects it detects at a predetermined distance range. Based on the results of research, a guide tool for blind people with fuzzy logic for the success rate in detecting objects on sensor 1 is 96.82%, while the success rate for sensor 2 is 97.97%. Keywords: Visual Aids, Microcontroller, Fuzzy Logic